Perbandingan Distribusi Dan Pola Kepekaan Acinetobacter baumannii Terhadap Antimikroba Di RSUD Dr. Soetomo Surabaya Periode Januari–Maret 2015, April–Juni 2015, dan Januari–Maret 2016 - Silvia Sutandhio; Agung Dwi Wahyu Widodo; Lindawati Alimsardjono; Eddy Bagus Wasito (JURNAL WIDYA MEDIKA, 2018)
Acinetobacter baumannii is an environmental bacteria that can cause opportunistic infections such as ventilator-associated pneumonia, burn wound infection, urinary tract infection, and sepsis in immunocompromised patients. A. baumannii infections are troublesome because the bacteria resistance to many antimicrobial agents. Surveillance of distribution and sensitivity pattern of A. baumannii is best to be done frequently in hospitals.Venous blood as much as 10 milliliters was drawn aseptically and transferred into liquid medium Bactec® to be sent to Clinical Microbiology Laboratory of Dr. Soetomo General and Teaching Hospital. Medium that showed bacterial growth was subcultured on Blood Agar Plate and MacConkey Agar, and incubated for 18-24 hours in aerobic condition. Identification and susceptibility test were done with semi-automated system BD Phoenix, and interpreted based onClinical and Laboratory Standards Institute 2015.A. baumannii collected on trimester January-March 2015 were 30 isolates, with 19 isolates being Multidrug Resistant(MDR) A. baumannii (63%) and 6 isolatesPandrug Resistant(PDR)A. baumannii (20%). Isolates from trimester April-June 2015 were 32 isolates, with 21 isolates being MDR A. baumannii (66%) and 2 isolates PDR A. baumannii (6%). Isolates from trimester January-March 2016 were 40 isolates, with 22 isolates being MDR A. baumannii (55%) and 2 isolates PDR A. baumannii (5%).A. baumannii mostly isolated from Intensive Care Unit, followed by Internal medicine ward, Pediatric ward, Surgery ward and Emergency Department. High sensitivity of A. baumanniion trimester January-March 2016 was to imipenem (50%), meropenem (50%), amikacin (53%), cotrimoxazole (53%), dan cefoperazone-sulbactam (55%).. MDRA. baumannii mostly isolated from ICU, which reflects high burden of antimicrobial use. At this moment, antimicrobial agents that can be used as empirical therapy for A. baumannii infection are imipenem, meropenem, amikacin, cotrimoxazole, and cefoperazone-sulbactam. The entire hospital member must implement the Infection Control and Prevention and Antimicrobial Stewardship Program to preventnosocomial infections byA. baumanniiand the emergence of MDRA. baumannii.